2008
DOI: 10.1007/s00216-008-2482-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of surface-confined ionic liquid stationary phases: impact of cation and anion identity on retention

Abstract: A series of surface-confined ionic liquid (SCIL) stationary phases for high-performance liquid chromatography were synthesized in-house. The synthesized phases were characterized by the linear solvation energy relationship (LSER) method to determine the effect of residual linking ligands and the role of the cation and the anion on retention. Statistical analysis was utilized to determine whether the system coefficients returned from multiple linear regression analysis of chromatographic retention data for a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The commonly used ILs for this purpose are based on 1,3-dialkylimidazolium or N -alkylpyridinium cations with variably associated anions [ 91 , 93 ]. In 2010, the first example of SCIL applied to the separation of small peptides was reported by Chitta et al .…”
Section: Ionic Liquids For Peptide Purification and Characterizatimentioning
confidence: 99%
“…The commonly used ILs for this purpose are based on 1,3-dialkylimidazolium or N -alkylpyridinium cations with variably associated anions [ 91 , 93 ]. In 2010, the first example of SCIL applied to the separation of small peptides was reported by Chitta et al .…”
Section: Ionic Liquids For Peptide Purification and Characterizatimentioning
confidence: 99%
“…To gain more insights into the retention characteristics of SCIL SPs, Stalcup et al conducted a series of systematic studies on the RP retention mechanisms involved in the SCIL SP (Sil-C 8 ImC x -Br)-MP system via LSER model [74][75][76]. The chromatographic evaluations revealed that the e, v terms were always positive, while s negative, a and b fluctuated around zero.…”
Section: Reversed-phase Modementioning
confidence: 96%
“…Recently, HPLC stationary phases have been reported in which aromatic cations (e.g., alkyl imidazolium or pyridinium) cations, with a variety of associated anions (e.g., bromide, chloride, tetrafluoroborate) have been attached to silica sorbents, forming surface-confined ionic liquid (SCIL) stationary phases. [29][30][31][32][33][34][35] Capillary electrophoresis and NMR studies have revealed that under aqueous conditions, imidazolium cations interact with halophenols through p-p stacking. [36] Linear solvation energy relation (LSER) studies using neutral aromatics have confirmed that SCIL phases exhibit multimodal retention [37] and behaved somewhat like phenyl phases under reversed-phase conditions.…”
Section: Introductionmentioning
confidence: 99%